The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/1049731512469279
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an Inpatient Social Early Warning System for Child Maltreatment

Abstract: Objectives: The current article describes the process evaluation of a social early warning system (SEWS) for the prevention of child maltreatment in the federal state of Hamburg. This prevention initiative targets expectant mothers and their partners including an initial screening of risk factors for child maltreatment, a subsequent structured clearing interview further exploring risks and identifying protective factors and an optional referral to the regional health and social care system. Method: The process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Patient navigation approaches focussing on unmet (social) needs in the paediatric setting have also demonstrated promising findings, such as an increase in referrals, a decrease of social needs, and an improvement of the child's health (Garg et al, 2015;Gottlieb et al, 2016;Gottlieb et al, 2020;Pantell et al, 2020). In Germany, pilot systems such as the family intervention "Babylotse" (baby pilot) have been established in many obstetric clinics and the gynaecologic and paediatric outpatient setting (Atabaki et al, 2012;Ayerle et al, 2010;Klapp et al, 2019). The evaluation of these approaches indicated a high participation and acceptance in pregnant women and families (Atabaki et al, 2012), reduced maternal depression and stress (Klapp et al, 2019), and an increase in self-efficacy and parental competencies (Ayerle et al, 2010) could also be observed.…”
Section: Palabras Clave: Estrés Prenatal Estré Prenatal Revisión Coop...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patient navigation approaches focussing on unmet (social) needs in the paediatric setting have also demonstrated promising findings, such as an increase in referrals, a decrease of social needs, and an improvement of the child's health (Garg et al, 2015;Gottlieb et al, 2016;Gottlieb et al, 2020;Pantell et al, 2020). In Germany, pilot systems such as the family intervention "Babylotse" (baby pilot) have been established in many obstetric clinics and the gynaecologic and paediatric outpatient setting (Atabaki et al, 2012;Ayerle et al, 2010;Klapp et al, 2019). The evaluation of these approaches indicated a high participation and acceptance in pregnant women and families (Atabaki et al, 2012), reduced maternal depression and stress (Klapp et al, 2019), and an increase in self-efficacy and parental competencies (Ayerle et al, 2010) could also be observed.…”
Section: Palabras Clave: Estrés Prenatal Estré Prenatal Revisión Coop...mentioning
confidence: 99%
“…In Germany, pilot systems such as the family intervention "Babylotse" (baby pilot) have been established in many obstetric clinics and the gynaecologic and paediatric outpatient setting (Atabaki et al, 2012;Ayerle et al, 2010;Klapp et al, 2019). The evaluation of these approaches indicated a high participation and acceptance in pregnant women and families (Atabaki et al, 2012), reduced maternal depression and stress (Klapp et al, 2019), and an increase in self-efficacy and parental competencies (Ayerle et al, 2010) could also be observed. However, there is little knowledge regarding the efficacy of those approaches compared to the regular healthcare.…”
Section: Palabras Clave: Estrés Prenatal Estré Prenatal Revisión Coop...mentioning
confidence: 99%
“…The offers are free of charge, for all families (to be) and aim to enable a low-threshold accessibility for families in particular psychosocial stress situations (National Centre for Early Prevention, 2018). Furthermore, they focus on creating multi-professional networks, to keep children safe, while especially enhancing the cooperation and the exchange between the health and social sector (Atabaki et al, 2013;Benz & Sidor, 2013; National Centre for Early Prevention [NZFH], 2018; Renner et al, 2018). Also early prevention initiatives must consider society's "friendly mother illusion" and need to be sensitive to the possibility of mothers as perpetrators.…”
Section: Future Directions In Prevention Of Maternal Sexual Abuse In Early Childhoodmentioning
confidence: 99%
“…An early warning system is a system built with the aim of reducing the risk of various disasters that may occur. From various previous studies, it was found that the use of EWS has been very widely used in various fields and needs such as the prevention of child maltreatment [12], the detection and prediction of deterioration in patient conditions in hospitals [13], dengue outbreaks [14], Methicillin-Resistant Staphylococcus Aureus (MRSA) outbreaks [15], floods [16,17], famine [18], political violence [19], conflict prevention [20], social anxiety [21] and crisis situations [22]. In this study, the aim is to identify the urgency of EWS development for social conflict early detection by using an Android application.…”
Section: Introductionmentioning
confidence: 99%